Effects of Antihistamines on Leukotriene and Cytokine Release from Dispersed Nasal Polyp Cells - Küsters, Sabine; Schuligoi, Rufina; Hüttenbrink, Karl-Bernd; Rudert, Jutta; Wachs, Angela; Szelenyi, Istvan; Peskar, Bernhard A. (Arzneimittelforschung, 2002)
In this study the effects of antihistamines on the release of eicosanoids and the pro-inflammatory cytokine tumor necrosis factor alpha (TNFα) were compared. Enzymatically dispersed cells from human nasal polyps served as an in vitro model of chronic respiratory mucosal inflammation. Nasal polyp cells (2 × 106/ml) were sensitized with human IgE preincubated with azelastine (CAS 58581-89-8), terfenadine (CAS 50679-08-8), levocabastine (CAS 79516-68-0) or cetirizine (CAS 83881-51-0), and stimulated with anti-human immunoglobulin E (IgE). Thromboxane B2 ( TBX2) and leukotriene C4 (LTC4) were measured by radioimmunoassay (RIA), TNFα by enzyme-linked immunosorbent assay (ELISA). Data represent mean values of % inhibition estimated from the untreated positive control or mean IC50 (n = 5). Azelastine and terfenadine inhibited TNFα release with IC50 values of 6.2 µmol/l and 4.3 µmol/l, respectively. T erfenadine reduced TXB2 release by 37 ± 15 %, and LTC4 release was decreased by azelastine and terfenadine very potently by 86 % and 100 %, respectively. Azelastine shows anti-inflammatory properties in therapeutically relevant concentrations as assessed by its ability to reduce TNFα release as well as its ability to inhibit LTC4 production in allergically stimulated human nasal polyp cells.
Keywords: Azelastine; Cetirizine; Leukotriene; Levocabastine; Nasal polyps, human; Terfenadine; Tumor necrosis factor α